THE RELATIONSHIP BETWEEN ORGANIZATIONAL COMMITMENT AND CAREER DEVELOPMENT AND EMPLOYEE JOB SATISFACTION AT THE JAKARTA KEBAYORAN BARU ONE PRIMARY TAX OFFICE - Brachma, Wahyu; Rangkuti, Zulkifli; Ratnawita, Ratnawita (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
Using a simple random sampling technique, a sample of 93 employees at the Pratama Jakarta Kebayoran Baru Satu Tax Service Office was taken. Based on the coefficients table above, Organizational Commitment (X1) is significantly related to Employee Job Satisfaction (Y), because the t value obtained for Organizational Commitment (X1) is 5,371, while the t table value for n = 93 is 2,009. So 5.371 > 2.009, then H0 is rejected and Ha is accepted. Career Development (X2) is significantly related to Employee Job Satisfaction (Y), because the t value obtained for the Career Development (X2) variable is 5,445, while the t table value for n = 93 is 2,009. So 5,445 > 2,009, then H0 is rejected and Ha is accepted. Organizational Commitment (X1), Career Development (X2) and together have a positive relationship to Employee Job Satisfaction (Y), because the Fcount value obtained is 320.209, while the Ftable ( 0.05) for n = 93 is 2.70. So Fcount > from Ftable or 320,209 > 2.70 with a significance level of 0.000 (0.000 < 0.05). The combined relationship value can also be seen from the Model Summary table 4.17, that the resulting Adjusted R Square value is 0.772. This shows that 77.2% of Organizational Commitment (X1), Career Development (X2) are simultaneously related to Employee Job Satisfaction (Y), while the remaining 22.8% is related to other factors not examined in this research